Tropical eosinophilia and Loeffler's syndrome. Clinical, haematological and functional study of nine cases - Bouroncle G., Bertha (1947)
For some time he has worried us the problem of Tropical eosinophilia and Loeffler's Syndrome, for this reason we decided to address the issue in its clinical, hematological and some biochemical blood aspect. The first step was to acquire the optimal technique as regards hematology the objective was achieved thanks to the occupation we play in a clinical laboratory. Then the serial and systematic study of all patients who came to our hands in the period of one year was made. The base of the research study consisted of 9 patients with Tropical Eosinophilia in that span. We present the clinical interpretation, haematological and biochemical findings in blood, performed serially.